2019
DOI: 10.1089/ars.2018.7515
|View full text |Cite
|
Sign up to set email alerts
|

Redox Signaling from and to Peroxisomes: Progress, Challenges, and Prospects

Abstract: As the precise molecular mechanisms underlying many of these associations are still poorly understood, a key focus for future research should be the identification of primary targets for peroxisome-derived HO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 188 publications
0
44
0
Order By: Relevance
“…In addition, the functional correlation between disease pathogenesis and alterations in peroxisome physiology has to be deciphered. Other rapidly developing research areas include the role of peroxisomes in cellular redox balance and redox signalling (Fransen and Lismont 2018 ) and in antiviral signalling and defence (Wong et al 2018 ). Peroxisomes are still among the more mysterious subcellular compartments in eukaryotic cells, but there is no doubt that they are “on the rise” and poised to reveal more surprises in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the functional correlation between disease pathogenesis and alterations in peroxisome physiology has to be deciphered. Other rapidly developing research areas include the role of peroxisomes in cellular redox balance and redox signalling (Fransen and Lismont 2018 ) and in antiviral signalling and defence (Wong et al 2018 ). Peroxisomes are still among the more mysterious subcellular compartments in eukaryotic cells, but there is no doubt that they are “on the rise” and poised to reveal more surprises in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, peroxisomes also contain nitric oxide synthase (NOS2), which generates NO. To counterbalance ROS production, peroxisomes possess several antioxidant enzymes, such as catalase (CAT), superoxide dismutase 1 (SOD1), peroxiredoxin 5 (PRDX5), glutathione S-transferase kappa 1 (GSTK1) and glutathione peroxidase (GPx) [144,145]. The role of peroxisomes within the cellular redox landscape is not fully understood, but it has been suggested that their function as a source or sink for H 2 O 2 is tissue-specific [144].…”
Section: Peroxisomesmentioning
confidence: 99%
“…To counterbalance ROS production, peroxisomes possess several antioxidant enzymes, such as catalase (CAT), superoxide dismutase 1 (SOD1), peroxiredoxin 5 (PRDX5), glutathione S-transferase kappa 1 (GSTK1) and glutathione peroxidase (GPx) [144,145]. The role of peroxisomes within the cellular redox landscape is not fully understood, but it has been suggested that their function as a source or sink for H 2 O 2 is tissue-specific [144]. Nevertheless, peroxisomal function and redox metabolism are important for metabolic reprogramming and are crucially involved in cancer development [146].…”
Section: Peroxisomesmentioning
confidence: 99%
“…For instance, in mammals, there are only about 50 different proteins in the organelle matrix . These proteins are mainly enzymes participating in metabolic pathways such as synthesis of plasmalogens and bile acids, β‐oxidation of very long chain fatty acids, and detoxification of glyoxylate and ROS .…”
Section: Peroxisomal Targeting Signals Their Receptors and The Impomentioning
confidence: 99%